PENGARUH FIRM SIZE, PROFITABILITY, FIRM AGE, FIRM GROWTH, LEVERAGE, DAN INDEPENDENT COMMISSIONER TERHADAP INTELLECTUAL CAPITAL DISCLOSURE PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2014 - Joson, Monica; Susanti, Merry (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The purpose of this study is to analyze the effect of firm size, profitability, firm age, firm growth, leverage and independent commissioner on intellectual capital disclosure of financial companies which are registered in Indonesia Stock Exchange from 2012-2014. The samples of this study are 57 companies. Secondary data are collected by learning the company’s financial statement. Collected data were processed by using SPSS for Windows 20. The result showed that firm size, firm age and independent commissioner partially influence the intellectual capital disclosure, while profitability, firm growth and leverage has no effect on intellectual capital disclosure.